Affective Anachronisms, Fateful Becomings: Otaku Movement and the Joan of Arc Effect in Type-Moon's Transhistorical Anime Ecology. Issue 1 (1st June 2021) - Boyd, David John
Abstract: This article examines the temporal and phenomenological philosophies of Gilles Deleuze, Félix Guattari, and Paolo Virno, specifically in relation to the transmedia franchises of the Japanese game studio, Type-Moon. Against linear, national, and majoritarian grand narratives of the historical, the otaku artists, writers, and developers responsible for the Fate series postulate whether it is possible to harness the intense and affective forces described by Jay Lampert as "the Joan of Arc effect" in the blink of an eye or in the palm of your hand. Through a philosophical and formal analysis of three spinoff series from the Fate franchise, this article investigates how Type-Moon's deployment of the "anime machine" encourages its viewers and users to see and feel the abundance of flowing "nomadic memories" or counter-historical visions from the perspective of minor populations. Through this highly embodied and tactile experience of transhistorical (un)becomings, Type-Moon's series offer a deterritorialized, post-national world-image of the otaku database which mediates between the overloading affects of becoming-woman and the digitally encoded logic of transversal through the frames, windows, interfaces, devices, platforms, and bodies that constitute Type-Moon's vibrant anime ecology.